The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18805/lr-449
|View full text |Cite
|
Sign up to set email alerts
|

Influence of priming with exogenous boron on the seed vigour of alfalfa (Medicago sativa L.)

Abstract: Alfalfa seeds were primed with 0, 0.1 %, 0.3 %, 0.6 %, 1.2 %, 2.4 % and 4.8 % (W/V) concentration of borax solution for 0 (control), 3, 6, 9 and 12 h at 20°C. The results showed that the vigour of alfalfa seeds were very significantly (P less than 0.01) related to boron concentration, priming time and their interaction, they were enhanced by the opportune concentration of boron priming, but were restrained by high concentration of boron. Priming with 0.1 % boron for 6 h was the best tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 17 publications
5
12
0
Order By: Relevance
“…Seedling vigour index generally reflected the ability of seedling establishment during plant growth. In this study, seedling vigour index of alfalfa seeds was significantly (P<0.05) declined with the extension of priming time (Table 1), this was similar to our previous results (Xia et al, 2019). Excessive boron priming could not provide sufficient energy for seeds in time to complete their germination and seedling growth (Chen and Arora, 2013).…”
Section: Influence Of Boron Priming On Seed Vigoursupporting
confidence: 90%
See 4 more Smart Citations
“…Seedling vigour index generally reflected the ability of seedling establishment during plant growth. In this study, seedling vigour index of alfalfa seeds was significantly (P<0.05) declined with the extension of priming time (Table 1), this was similar to our previous results (Xia et al, 2019). Excessive boron priming could not provide sufficient energy for seeds in time to complete their germination and seedling growth (Chen and Arora, 2013).…”
Section: Influence Of Boron Priming On Seed Vigoursupporting
confidence: 90%
“…Previous studies have showed that the seed yield of alfalfa can be effectively improved by foliar application of boron (Du et al, 2009). Moreover, our previous study has also found that the seed vigour of alfalfa can be availably improved by appropriate priming with boron, but the boron toxicity also Influence of Boron Priming on the Antioxidant Ability of Alfalfa Seeds occurs in those primed with high concentrations (Xia et al, 2019). Nonetheless, this is still unreported on the relationship between the antioxidant activity and seed vigour of alfalfa causing by boron priming.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations